1999
DOI: 10.1089/neu.1999.16.123
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hemoglobin Oxygen Affinity Does Not Increase Hydroxyl Radicals After Acute Subdural Hematoma in the Rat

Abstract: Extensive evidence is available to show the importance of ischemia after severe human head injury. We have previously shown that pharmacologically increasing the release of oxygen in brain tissue where the local oxygen pressure is low reduces infarct size in animal models. To study the possible negative effects of this strategy, we tested the effect of an allosteric modifier of hemoglobin (RSR13) on free radical production in the rat acute subdural hematoma (ASDH) model, both under normoxic as well as under hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In this model, autologous blood is injected underneath the dura, forming a haematoma. As in SDH patients (Graham et al, 1978(Graham et al, , 1987Adams et al, 1983), cortical lesions and damage to the hippocampal formation have been observed in SDH rats (Bullock et al, 1991;Kuroda and Bullock, 1992;Doppenberg et al, 1999). Damage to these brain structures has been associated with cognitive decline in patients (Graham et al, 1978;Adams et al, 1983).…”
mentioning
confidence: 89%
“…In this model, autologous blood is injected underneath the dura, forming a haematoma. As in SDH patients (Graham et al, 1978(Graham et al, , 1987Adams et al, 1983), cortical lesions and damage to the hippocampal formation have been observed in SDH rats (Bullock et al, 1991;Kuroda and Bullock, 1992;Doppenberg et al, 1999). Damage to these brain structures has been associated with cognitive decline in patients (Graham et al, 1978;Adams et al, 1983).…”
mentioning
confidence: 89%
“…33 Furthermore, direct measurement of free radical generation failed to reveal any difference in hydroxyl radical formation (2,3-DHBA, salicylate-trapping method) between control and treatment with the same allosteric modifier of hemoglobin. 34 While these studies are limited to animal models, to the best of our knowledge, no study has been performed in humans demonstrating an association with increased brain tissue oxygenation and free radical formation. 33,34 Future work identifying clinical outcomes in patients with brain tissue monitoring and laboratory experiments will determine the therapeutic potential of increases in brain tissue oxygen tension.…”
Section: Limitationsmentioning
confidence: 99%
“…34 While these studies are limited to animal models, to the best of our knowledge, no study has been performed in humans demonstrating an association with increased brain tissue oxygenation and free radical formation. 33,34 Future work identifying clinical outcomes in patients with brain tissue monitoring and laboratory experiments will determine the therapeutic potential of increases in brain tissue oxygen tension.…”
Section: Limitationsmentioning
confidence: 99%
“…Whatever the eventual answer, it is likely that the estimation of P50 as an indicator of oxygen-haemoglobin affinity, and hence tissue oxygen availability, will be a useful adjunct to the intensivists' diagnostic armamentarium. With knowledge of the P50, manipulation of this index may lead to significant reductions in the morbidity or mortality of critically ill patients [15][16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%